Soomi's sweater - Oh, Susie (Clavis, 2021)
Soomi's new sweater arrives, but it doesn't quite fit. Mom makes it just right and Soomi can't wait to show her friends. Soon, Soomi's brand new sweater isn't so new anymore. Her friends try to patch it up, but nothing works. Thankfully, Mom knows just what to do. She creates something better than new!